Communication and the Impact of Social Media in the Society - Micheal A Nza-Ayang; Cyprian Chidozie; Chukwuezi Emmanuela Eziaku (International Journal of Advance Social Sciences and Education (IJASSE), 2024)
The place of social media in today world cannot be over emphasized as such the need for this study. The study is based on 150 questionnaires research questions and test of hypothesis This data was analyzed in relation to the questionnaire. The technique for analyzing the data collected for this research work is simple statistics with the use of percentage and diagrammatical analysis. Data analysis was analyzed and interpreted with the use of simple percentage and statistical description. The study concluded and recommended that in order to help students cope and learn the most effective ways to use social media among other things, social media should be taught in universities, polytechnics, and other schools that provide courses in mass communication, public relations, and local government administration.